A survey of aflatoxin B1 in maize and awareness of aflatoxins in Vietnam - Hu Suk Lee; Hung Nguyen-Viet; Lindahl, Johanna F.; Ha Minh Thanh; Tran Ngoc Khanh; Le Thi Thu Hien; Grace, Delia (Brill, 2017)
Vietnam is a tropical country with high temperature and precipitation, which may provide good conditions for fungal growth. A few limited studies have been conducted to evaluate the level of aflatoxin B1 in maize in Vietnam. In addition, no studies have been conducted to evaluate the perception and knowledge of aflatoxins in Vietnam. Therefore, the main objective of this study was to determine the levels of aflatoxin B1 for human and animal consumption in maize and evaluate perceptions and knowledge of aflatoxins among people across the country. A total of 2,370 samples were collected from six provinces and analysed using ELISA. Among collected samples, 799 samples (33.71%, 95% confidence interval (CI): 31.81-35.66%) and 687 samples (28.98%, 95%CI: 27.17-30.86%) had levels above 2 µg/kg and 5 µg/kg, respectively [range from below limit of detection (LOD) to 34.8 µg/kg; of the samples above LOD, the mean was 13.1 µg/kg and median was 11.2 µg/kg]. A total of 551 people were interviewed from 6 provinces. The survey showed that awareness of aflatoxins (question: Have you heard about aflatoxins?) in southern Vietnam [An Giang (25%), Dak Lak (23.23%) and Dong Nai (6%)] was relatively higher than in provinces in northern Vietnam. We believe that this analysed information can be useful to better understand the epidemiology of aflatoxins in different provinces. This study also produces evidence on potential risk to humans and animals in Vietnam as well as demographic factors (such as gender and level of education) significantly influencing knowledge of aflatoxins. In conclusion, this paper points to the importance of raising the awareness of the risks with aflatoxins, bearing in mind the gender aspect during capacity development.